The antioxidant and neurochemical activity of Apium graveolens L. and its ameliorative effect on MPTP-induced Parkinson-like symptoms in mice - Pennapa Chonpathompikunlert; Phetcharat Boonruamkaew; Wanida Sukketsiri; Pilaiwanwadee Hutamekalin; Morakot Sroyraya (BMC, 2018)
Abstract Background Apium graveolens L. is a traditional Chinese medicine prescribed as a treatment for hypertension, gout, and diabetes. This study aimed to determine the neuroprotective effects of A. graveolens extract against a Parkinson's disease (PD) model induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) in C57BL/6 mice. Methods Male C57BL/6 mice treated with MPTP were orally dosed with A. graveolens extract daily for 21 days. Behavioral tests, including a rotarod apparatus, a narrow beam test, a drag test, a grid walk test, a swimming test, and a resting tremor evaluation, were performed. Thereafter, the mice were sacrificed, and monoamine oxidase A and B activity, lipid peroxidation activity, and superoxide anion levels were measured. Immunohistochemical staining of tyrosine hydroxylase was performed to identify dopaminergic neurons. Results We found that treatment with A. graveolens at dose of 375 mg/kg demonstrated the highest effect and led to significant improvements in behavioral performance, oxidative stress parameters, and monoamine oxidase A and B activity compared with the untreated group (p < 0.05). Moreover, the extract increased the number of neurons immunopositive for tyrosine hydroxylase expression compared with MPTP alone or MPTP with a positive control drug (p < 0.05). Conclusions We speculated that A. graveolens ameliorated behavioral performance by mediating neuroprotection against MPTP-induced PD via antioxidant effects, related neurotransmitter pathways and an increase in the number of dopaminergic neurons.